Macromedia Flash 8 : Training from the Source - English, James (Adobe Press, 2005)
What began life as a simple Web animation tool has evolved into a powerful platform for Web application development-which means that if you're serious about developing for the Web, you need to get serious about learning Flash. With its breakthrough motion-graphics capabilities and powerful run-time effects, Flash 8 provides the tools, authoring power, and rich video capabilities you need to provide stunning interactive content. This Macromedia-certified guide provides the key to learning the basics of Flash 8. Through a series of hands-on projects, master trainer James English provides a firm foundation in everything Flash-from graphics, animation, and video to ActionScript fundamentals. Simple step-by-step instructions and tons of screenshots guide you through the process of creating buttons and links, drawing and animating in Flash, formatting text, adding video and sound, loading data, and more-in short, everything you need to develop sophisticated, professional-looking Web sites. A companion CD includes the lesson files needed to complete the book's projects as well as a trial version of the program itself.